Towards more compact South African settlements through informal housing: The case of backyard densification in Bridgton and Bongolethu, Oudtshoorn - Louis Lategan; Juanee Cilliers (Town and Regional Planning, 2016)
This article engages the concepts of urban sprawl and density, as the foundations for a discussion on South Africa’s informal backyard rental sector. This research attempts to relate some of the spatial impacts levied by the backyard sector in post-apartheid South Africa, based on case study research in Oudtshoorn, Western Cape, the Rose Valley formalisation project, as well as the Bridgton and Bongolethu townships. This article employs both qualitative and quantitative analyses and arrives at several key findings. Results show that informal backyard rentals increase dwelling unit and population densities substantially in the case study, accommodating households who would otherwise occupy land illegally on the urban periphery, contributing to urban sprawl. Findings also suggest that these backyard tenants enjoy excellent access to services, placing increased pressure on Oudtshoorn’s already overcapacitated infrastructure network. This article posits that informal backyarding has to be encouraged and supported based on the sector’s contribution to urban compaction, but that related impacts on infrastructure be addressed in future planning interventions.